Expectation vs Reality: Cosmopolitan and Insular Social Capital among Malaysian Chinese Youth - July Edo; Rachel Chan Suet Kay; Rosila Bee MD. Hussain (Glocalism: Journal of Culture, Politics and Innovation)
This article discusses the form of social capital present among Malaysian Chinese youth, comparing across those who are Chinese-medium educated and English-medium educated. The reason for comparison is because of the dichotomy of Confucian values in Chinese-medium education and Western liberal democratic values in English-medium education, which may influence their choice of social network. Using a self-designed survey questionnaire, I assessed whether Putnam’s two forms of social capital, the bridging and the bonding social capital, are found in these two sub-ethnic groups. In terms of face-to-face interaction, it is found that ethnic identification remains a strong influence on respondents’ choice of social network. However, respondents also demonstrate an aspiration to network on a more global scale if facilitated by information communication technology. Given Malaysia’s present globalised environment, with strong migratory flows inside and outside, the reality of respondents’ social capital does not match the expectations respondents have of themselves. While they express a desire to network in a global nexus, in order to be more connected to the rest of the world, they are still restrained by attributes like ethnic identification and language preference.